Intensity Profile during an Ultra-endurance Triathlon in Relation to Testing and Performance - Barrero, A.; Chaverri, D.; Erola, P.; Iglesias, X.; Rodríguez, F. A. (International Journal of Sports Medicine, 2014)
We examined the heart rate (HR)-based intensity profile during an ultra-endurance triathlon (UET) estimated from the individual HR-oxygen uptake (˙VO2) relationship during specific graded tests, relating it to race performance. 9 male ultra-endurance triathletes completed the study. Before racing, subjects performed graded exercise tests involving cycle (C) ergometry, treadmill running (R) and free swimming (S) for peak ˙VO2 and HR at ventilatory thresholds (VT). Exercise-specific HR-˙VO2 regression equations were developed. Mean race HR was higher during S (149.2 (10.1) bpm) than during C (137.1 (5.7) bpm) and R (136.2 (10.5) bpm). During C and R, HR was below both VT (11% and 27–28%). HR differences between S and C correlated with C, R and final times. The greatest differences between S and C were related to the worst times in the next stages. These ultra-endurance triathletes performed S at a higher relative intensity, which was inversely correlated with performance in the following stages. The best predictors of final racing time (81%) were weight-adjusted ˙VO2max and HR difference between C and S. A more adequate characterization of the time pattern during the whole race, especially during S, adds new information concerning the intensity profile and cardiovascular demands of an UET race.
Keywords: heart rate; oxygen uptake; ventilatory threshold; swimming; cycling; running